GAMBARAN TINGKAT KECEMASAN ANGGOTA KELUARGA PADA PENULARAN TB PARU DI PUSKESMAS WENANG DENGAN PERSEPSI KATEGORI BAIK - Manarisip, Elvina Magdalena; Bidjuni, Hendro; Karundeng, Michael (JURNAL KEPERAWATAN, 2014)
Abtract : Background.In Indonesia Pulmonary TB is a major public health problem. The number of TB patients in Indonesia is the 5th largest in the world. Many factors will affect the family anxiety Pulmonary TB transmission, among others, the perception of the disease. Purpose. This study aims to determine Representation the stage of family anxiety In pulmonary TB transmission in Wenang health centers with good category in perception Method. This research uses descriptive analytic method using a cross-sectional study design to determine the relationship of perception of TB disease with anxiety on family members of TB transmission in the health center Wenang. The samples done by purposive sampling, obtained a total sample of 42 people from 84 population aged 15-60 years. Research. Perceptions of illness showed all respondents have a good perception of the disease. As for the anxiety level of all respondents totaling 42 people have high levels of anxiety are different. With the level of anxiety was the greatest as many as 16 respondents (38.1%), the next level of mild anxiety as much as 12 respondents, and severe anxiety level 8 respondents, while frantic as 6 respondents (14.3%). Key Word: Perception, family, anxiety, transmission. Abstrak : Di Indonesia TB Paru merupakan masalah utama kesehatan masyarakat. Jumlah pasien TB Paru di Indonesia merupakan ke-5 terbanyak di dunia. Banyak faktor yang berpengaruh terhadap kecemasan keluarga akan penularan TB Paru, antara lain persepsi penyakit. Tujuan. Penelitian ini bertujuan untuk mengetahui gambaran tingkat kecemasan anggota keluarga pada penularan TB Paru di Puskesmas Wenang dengan persepsi kategori baik. Metode. Jenis penelitian ini menggunakan metode deskriptif. Penentuan sampel dilakukan dengan cara purposive sampling, didapat jumlah sampel sebanyak 42 orang dari 84 populasi yang berusia 15-60 tahun. Hasil Penelitian. Persepsi penyakit menunjukkan semua responden memiliki persepsi penyakit yang baik. Sedangkan untuk tingkat kecemasan seluruh responden yang berjumlah 42 orang memiliki tingkat kecemasan yang berbeda-beda. Dengan tingkat kecemasan sedang yang paling besar yaitu sebanyak 16 responden (38,1%), selanjutnya tingkat kecemasan ringan sebanyak 12 responden, dan tingkat kecemasan berat 8 responden, sedangkan panik sebanyak 6 responden (14,3%). Kata kunci: Persepsi, keluarga, kecemasan, penularan.